Disharmony of Norms and Application of Punishment of Perpetrators of Assisting (Medeplichtige) Corruption Crimes in Indonesia - Ansori, Ansori; Sugiri, Bambang; Aprilianda, Nurini; Noerdajasakti, Setiawan (Nurani Hukum, 2025)
This study investigates the legal disharmony and uncertainty surrounding punishment for those who assist in corruption crimes in Indonesia. Currently, there's a conflict between the Criminal Code, which imposes a one-third lighter sentence for accomplices, and the Anti-Corruption Law, which threatens them with the same punishment as the main perpetrator. This normative inconsistency often leads to disparate and disproportionate sentencing, with some accomplices receiving harsher punishments than the main offenders, despite their lesser role. The novelty of this research is its exploration of this specific legal conflict and its impact on judicial outcomes. Addressing this issue is urgent to ensure fairness and legal certainty in corruption cases. This research's will contribute toward proposed reconstruction of the punishment norms for accomplices, based on the principle of proportionality, to reduce inconsistencies and prevent unjust disparities in sentencing.